Leadership theories, frameworks, and approaches in practice - Guthrie, Kathy L.; Whitney, Rich (Contemporary perspectives on leadership learning., 2025)
Leadership Theories, Frameworks, and Approaches in Practice is a comprehensive guide to theory and practice in leadership studies. Drawing from over a century of leadership literature and the insights of countless scholars and practitioners, this book offers a rich tapestry of knowledge from multiple disciplines. The book is an essential resource for students, practitioners, training developers, faculty, and scholars. It explores the evolution of leadership theories, paying homage to the thousands of contributors who have shaped the field. Each chapter delves into the history and application of specific leadership theories, providing a deep understanding of how they work in practice. Leadership Theories, Frameworks, and Approaches in Practice is a tribute to the social scientists and authors who have memorialized their work in books, articles, and resources, crafting leadership into the phenomenon it is today. By bridging theory and practice, it aims to refine and enhance leadership for all.